2009
DOI: 10.1186/1476-7961-7-6
|View full text |Cite
|
Sign up to set email alerts
|

An extract of the medicinal mushroom Agaricus blazei Murill can protect against allergy

Abstract: BackgroundAgaricus blazei Murill (AbM) is an edible Brazilian mushroom that has been used in traditional medicine for a range of diseases. It has been shown to have anti-infection and anti-tumor properties in the mouse, which are due to induction of Th1 responses. On the other hand, IgE-mediated allergy is induced by a Th2 response.ObjectiveSince according to the Th1/Th2 paradigm an increased Th1 response may promote a reduced Th2 response, the aim was to examine whether AbM had anti-allergy effects.MethodsA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 27 publications
5
39
0
Order By: Relevance
“…Oral administration of a protein isolated from the edible mushroom Flammulina velutipes inhibited the development of an allergic reaction to the model food (egg) allergen ovalbumin in mice (42). A similar result was obtained with an extract from A. subrufescens (also known as A. blazei ) and ovalbumin allergy (43). The same mushroom also protected mice against pneumonia caused by Streptococcus pneumonia upon oral administration of a water extract.…”
Section: Discussionsupporting
confidence: 75%
“…Oral administration of a protein isolated from the edible mushroom Flammulina velutipes inhibited the development of an allergic reaction to the model food (egg) allergen ovalbumin in mice (42). A similar result was obtained with an extract from A. subrufescens (also known as A. blazei ) and ovalbumin allergy (43). The same mushroom also protected mice against pneumonia caused by Streptococcus pneumonia upon oral administration of a water extract.…”
Section: Discussionsupporting
confidence: 75%
“…Agaricus subrufescens is valued not only for its taste but also for health reasons. Antifungal properties (Bernardshaw et al, 2005), antivirals (Sorimachi et al, 2001), antioxidant properties (Oliveira et al, 2007;Soares et al, 2009) and antiallergic properties (Ellertsen and Hetland, 2009;Mizuno, 2010). In addition, it lowers blood cholesterol, stimulates the immune system, and is effective for treating AIDS (Mizuno, 2010;Liu et al, 2008;Lima et al, 2011).…”
Section: Biological Materialsmentioning
confidence: 99%
“…We found that Andosan™ AbM-based extract protected against allergy in mice because there was less IgE antibodies (Th2 response) against the ovalbumin allergen in mice given Andosan™ before ovalbumin immunization (Figure 3) [64]. There was also a tendency to more control IgG2a antibodies (Th1 response in the mouse) against ovalbumin in mice given Andosan™ before the ovalbumin immunization.…”
Section: Allergymentioning
confidence: 78%
“…1 day before or 3 weeks after immunization s.c. with the model allergen, ovalbumin. After 26 days the mice were sacrificed, bled for serum, their spleens removed, and the spleen cells cultivated 1 day further with Andosan or phosphate-buffered saline (PBS) ( Table 1) [64]. ELISA analyses were used for specific anti-ovalbumin IgE (Th2 response) or control IgG2a (Th1 response) antibodies in serum, and IL-4 and IL-5 Th2 type cytokines, and IL-2 and IFNγ Th1 type cytokines in spleen cell culture supernatants.…”
Section: Allergymentioning
confidence: 99%